Thermal elastohydrodynamic lubrication simulation model for the tooth guidance contact of a single tooth gearbox under mixed friction conditions. (March 2022) - Keller, Michael; Wimmer, Thomas; Bobach, Lars; Bartel, Dirk
This article presents a simulation model for thermal elastohydrodynamic lubrication of the tooth guidance (piston/cylinder) contact of a single tooth gearbox. A finite-element analysis provides the boundary conditions for the thermal elastohydrodynamic lubrication simulation. The finite-element analysis under dry conditions allows calculating the macroscopic deformed contact surfaces for the elastohydrodynamic simulation model. The Hertzian deformation should be calculated in the presence of a lubricant and not with a dry finite-element analysis. A recently presented method, based on the finite-element submodeling technique, is extended to remove the Hertzian deformation of the macroscopic deformed lubrication gap from the dry finite-element analysis. A mixed friction with measured rough surfaces using the averaged flow model and mass conserving cavitation is implemented as well. An example shows how optimization of the gearbox by application of the simulation model is possible.